Prevalence of neuropathic symptoms in patients referred for temporomandibular disorder in a Chilean hospital, 2014-2015. - Sebastian Miranda; Carol Gayoso; Patricio Ruiz; Diego Halabi (Universidad de Concepción., 2015)
Aim: To determine the prevalence of neuropathic symptoms in the orofacial region in patients referred for painful temporomandibular disorder at Hospital Base Valdivia in 2014 and 2015. Materials and method: An observational study was conducted on patients referred for painful temporomandibular disorder by general dentists working in primary dental health care at Hospital Base Valdivia, during October 2014 and March and April 2015. Patients were asked to complete the LANSS pain scale by one of the examiners. The variables age, sex and location of pain were measured and registered. Results: Of the 84 patients surveyed, 88.1% were women, with a mean age of 38.2 years. The median score obtained with the LANSS scale was 3.0 [0-8.75]. A 20.2% had neuropathic pain symptoms. They were all women with an average age of 36.7. The most recurrent painful area was the right mandibular dermatome of the trigeminal nerve in patients with neuropathic pain symptoms. Conclusion: The prevalence of symptoms of neuropathic pain was 20% in patients referred for painful temporomandibular disorders. Dentists should evaluate neuropathic symptoms to provide a proper management of the condition.